A comprehensive hierarchical model of beach resort hotel stays. (December 2018) - Channoi, Rachata; Clemes, Michael D.; Dean, David L.
Abstract: This research develops and tests a comprehensive hierarchical model for long duration, high involvement beach resort hotel stays in Thailand. The interrelationships among five higher order marketing constructs: service quality, customer satisfaction, customer perceived value, corporate image and customer loyalty are investigated. A third order conceptualisation of service quality is included in the analysis. The results of the structural equation modelling demonstrate that service quality has a positive impact on customer satisfaction. Customer satisfaction and corporate image are the two key determinants of customer loyalty. Customer satisfaction is also a full mediator in the relationship between service quality and customer loyalty and customer perceived value and customer loyalty. The sub and primary dimensions of service quality also vary in importance. This is the first research that integrates a second-order conceptualisation of service quality with higher order attitudinal and behavioural constructs for beach resort hotel stays. Management can also employ the results of the empirical analysis in their tactical and strategic marketing initiatives in order to provide a superior level of service quality and increase customer loyalty.